Spectral Dependence of Optical Absorption of 4H-SiC Doped with Boron and Aluminum - I. G. Atabaev; Kh. N. Juraev; M. U. Hajiev (Journal of Spectroscopy)
Optical absorption of p-n-4H-SiC structures doped with boron and aluminum by low-temperature diffusion was studied for the first time. Diffusion of impurities was performed from aluminum-silicate and boron-silicate films (sources) fabricated by various methods. In the spectral dependences of optical absorption at room temperature, bands associated with transitions from impurity levels, as well as absorption bands associated with defects of the vacancy nature, were observed. The level of absorption in the samples was used to estimate concentration of defects. It was shown that the use of sources of impurity atoms created by using boron and aluminum chlorides allows one to reduce the concentration of vacancy defects.